Influence The Composite Of The Media For The Growth Of Timor-Leste's Hybrid Coffee (Coffee Sp) With Other - Madeira Soares, Mario; de Jesus Gomes , Julio (Jurnal Syntax Fusion, 2024)
The aim this investigation was to determine the effect of means composition about to the growth of hybrid Timorese coffee cuttings with other varieties in the prey nursery to the means application for the growth of the four varieties of coffee, thus the write takes the Title of the research with the hypothesis " multiplication to acquire new data through the means composition for growth coffee plant cuttings of on the four varieties" The investigation was conducted in date 4 June 2014 at 12 October 2014 out in the nursery " ETCI " the Village of Talimoro , Sub-district Ermera, Ermera Municipality, experience degin using by using a completely randomized design (CRD) with 2 factor treatment, there are two factors the main factor is to use a combination of medium composition ratio with a ratio of compost two (2), sand one (1) and topsoil one (1), or 2 : 1 : 1 and the second factor of four types of coffee. Coffee Hybrid Timorense, Arabica, Robusta and Mocha high observation parameter on shoots, buds diameter, number of shoots, number of leaves and leaf area. Based on the results of this investigation indicate that development through cuttings of several varieties that were tested turned out that provide significant cuttings shoots (1.8) cm, diameter of shoots (0.30) mm, the number of shoots (1:40), number of leaves (2.6) , leaf area (9.9) cm